Pterostilbene attenuates intestinal epithelial barrier loss induced by high loading intensity of exercise - Zhang, Lidong; Tian, Guoliang; Huang, Li; Zhou, Min; Zhu, Jundong; Yi, Long; Mi, Mantian (Frontiers in Nutrition, 2022)
Mounting evidence suggested that high loading intensity of exercise might be detrimental to human health, especially the gastrointestinal tract. Pterostilbene (PTE), derived from grapes and blueberries, might reach a high concentration of intestinal contents. Our study aimed to evaluate PTE's ability to prevent the loss of intestinal epithelial barrier in high loading intensity of exercise. The exercise model was established by the forced running of mice. An effective HPLC-UV method was developed to quantify PTE concentration in intestinal content. The mRNA changes were detected by quantitative polymerase chain reaction (qPCR). The structure of intestinal flora was analyzed by 16S rRNA sequencing. The PTE (100mg/kg/d) could significantly attenuate exercise-induced intestinal epithelial barrier loss. Moreover, the HPLC-UV assay showed that the PTE concentration of intestinal content could last 12 hours. Furthermore, exercise increased the abundance of Alistipes, which was related to lipopolysaccharide (LPS) production but could not be reversed by PTE intervention. Besides, cell experiments showed that pterostilbene could promote the expression of intestinal epithelial tight junction (TJ) molecules in vitro. In conclusion, PTE has a significant interest in preventing exercise-induced intestinal damage.